2017
DOI: 10.12659/msm.899563
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uric Acid in Hypertension of Adolescents, Prehypertension and Salt Sensitivity of Blood Pressure

Abstract: Uric acid is the end product of purine metabolism. Metabolic disorders of uric acid are associated with many disease states. Substantial evidence suggests the possible role of uric acid as a mediator of high blood pressure. Elevated uric acid is closely associated with new onset essential hypertension in adolescents and prehypertension; and urate-lowering agents can significantly improve these early stages of hypertension. Uric acid also influences salt sensitivity of blood pressure through two phases. Local r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 62 publications
0
17
0
1
Order By: Relevance
“…The association between uric acid levels and damage accrual in patients with SLE was evaluated, and serum uric acid level was found to be associated with the development of new damage in these patients. Previous studies have found an association between hyperuricaemia and hypertension,13 metabolic syndrome14 and renal disease,2 as well as with organ failure or damage,15 especially renal 16…”
Section: Discussionmentioning
confidence: 99%
“…The association between uric acid levels and damage accrual in patients with SLE was evaluated, and serum uric acid level was found to be associated with the development of new damage in these patients. Previous studies have found an association between hyperuricaemia and hypertension,13 metabolic syndrome14 and renal disease,2 as well as with organ failure or damage,15 especially renal 16…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in non-pregnant individuals, uric acid is known to be related to severity of cardiovascular disease and may be involved in the transition from pre-hypertension to hypertension even though the pathophysiology is not yet elucidated. 26,27 Therefore, salivary uric acid might not only reflect placental pathology but also maternal cardiovascular dysfunction.…”
Section: Ta B L E 3 Levels Of Salivary Uric Acidmentioning
confidence: 99%
“…The ultimate effect is reduced compliance of renal afferent arterioles, shifted pressure natriuresis curve, and sodium-sensitive hypertension. This level cannot be modified by SUA lowering agents [12][13][14][15]. A hypertensive effect of uric acid has been described in rats; however, it seems to be transferable to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that uric acid promotes hypertension regardless of other known risk factors, and its lowering may be beneficial as the only intervention. SUA was initially associated with essential hypertension as well as with prehypertension, especially in the overweight/obese [12,18]. The predictive value of increased uric acid is not limited to hypertension, but it refers also to cardiovascular disease, obesity, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%